GEOTHERMAL CHARACTERISTICS OF THE RIES IMPACT STRUCTURE - Popov Yu.; Romushkevich R.; Pohl J.; Soffel H.; Tertychnyi V. (My University, 2003)
A new investigation of the thermal conductivity of the drill cores from the research drill hole Nördlingen 1973 in the Ries impact structure was conducted. The 1206 m deep drill hole penetrated 331 m of post-impact lake formations, then 275 m of suevitic impact formations with varying amounts of large crystalline basement blocks and then 600 m of fractured, displaced basement blocks containing appreciable amounts of dyke breccias. The main purpose of the measurements was to see the signature of the shock effects in the thermal properties of the impact formations. The use of the new non-contact optical scanning instrument allowed measurements with a resolution of a few centimetres. A complicated preparation of the samples was not required. Thermal conductivity values on dry and on water-saturated drill cores and thermal inhomogeneity factors were obtained for samples with a spacing of about 2 m. It could be shown that the thermal conductivity is extremely inhomogeneous on various scales and that there is a close relation with the degree of shock and thermal transformation of the target rocks. An improved theoretical model for the thermal conductivity of rocks taking into account the form of grains, pores and cracks and using measurements on dry and saturated cores yields information on the porous space of the rock samples. Correlations between the thermal conductivity and other petrophysical properties determined from well logging data were found. They allow other physical properties to be predicted from the conductivity values. The new thermal conductivity data together with temperature logging data also gave the possibility of making new estimates of the undisturbed heat flow density in the crater area (90-95 mW m-2), with about 30 per cent higher values than previous estimates. A significant increase of the heat flow density in the upper part of the structure indicates fluid migration from deeper parts. The absence of thermal anisotropy in crystalline rocks, increasing thermal conductivity with depth and increasing heat flow density may be characteristic features of impact structures.